Analisis Sistem Pengendalian Internal Pembelian Barang (Purchasing) Pada Harris Hotel & Conventions Gubeng Surabaya - Fitri Erliya Wati; Sari Andayani (Jurnal Riset Akuntansi, 2024)
The study aims to evaluate the effectiveness of the internal purchasing control system at HARRIS Hotel & Conventions Gubeng Surabaya. The method used is qualitative descriptive with data collection through observation and library study. The results showed weaknesses in the separation of tasks between the purchasing and receiving sections, as well as a lack of general manager involvement in the procurement process. Despite the effective use of computerized systems, insufficient organizational structure and work practices that are not fully compliant with standards can impede the effectiveness of internal controls.